Promoting Inclusion Oral Health: Social Interventions to Reduce Oral Health Inequities - Ruth Freeman (MDPI AG, 2020)
To advance our understanding of inclusion oral health and to address the impact of social exclusion upon oral health, this group of papers sets out to provide an argument for the need for social and community-based interventions, theoretically underpinned by pluralistic definitions of evidence-based practice and the radical discourse of health promotion for those experiencing exclusion. Using the definition and framework of inclusion oral health, these papers illustrate the requirement for mixed-methods research, the incorporation of experts by experience in the research process, and the need for co-design and co-produced interventions. The papers in this Special Issue present various sources of evidence used to transform top-down into bottom-up community-based interventions for people experiencing homelessness, people in custody, and families residing in areas of high social deprivation. The first two papers provide the evidence for extreme oral health in those experiencing exclusion, and the final four papers report on the implementation and evaluation of social or community-based interventions. This collection of research papers will be of interest to all those wishing to reduce health inequities. This will be achieved by focusing on prevention, adopting a common risk factor agenda, and incorporating co-design and co-production elements into interventions, to tackle the oral health inequities felt by those most excluded in our societies.